Hyperbole Analysis In Gracie Abrams Good Riddance Deluxe Album - Ginarsiwi Mayangseto; Rahmaditya Khadifa Abdul Rozzaq Wijaya; Ratini Setyowati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to find out the hyperboles as one of the figurative language devices and the utilization of hyperboles in song structure (verse, chorus, bridge, outro) in Good Riddance Deluxe album by Gracie Abrams. This study employs qualitative descriptive method was utilized in analyzing and describing the hyperbole. Reflecting from the findings there are nineteen hyperboles in total, which classified and divided into each song structure. The results carried fourteen hyperboles in verse, three hyperboles in bridge along with two hyperboles in chorus. Reflecting beforehand explanation, hyperboles written in verse is dominating this study.